2018
DOI: 10.2337/db18-0729
|View full text |Cite
|
Sign up to set email alerts
|

Preproglucagon Neurons in the Nucleus of the Solitary Tract Are the Main Source of Brain GLP-1, Mediate Stress-Induced Hypophagia, and Limit Unusually Large Intakes of Food

Abstract: Centrally administered glucagon-like peptide-1 (GLP-1) supresses food intake. Here we demonstrate that GLP-1-producing (PPG) neurons in the nucleus tractus solitarii (NTS) are the predominant source of endogenous GLP-1 within the brain. Selective ablation of NTS PPG neurons by viral expression of diphtheria toxin subunit A (DTA) substantially reduced active GLP-1 concentrations in brain and spinal cord. Contrary to expectations, this loss of central GLP-1 had no significant effect on ad libitum feeding of mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
198
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(229 citation statements)
references
References 52 publications
15
198
0
2
Order By: Relevance
“…PPG NTS neurons selectively encode large meal satiation PPG NTS neurons are not necessary for control of daily or long term food intake or bodyweight in ad libitum eating mice 7 . However, it is unknown whether they regulate within-or between-meal parameters, or whether the absence of an ablation-induced bodyweight phenotype masks more subtle alterations in energy expenditure or physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…PPG NTS neurons selectively encode large meal satiation PPG NTS neurons are not necessary for control of daily or long term food intake or bodyweight in ad libitum eating mice 7 . However, it is unknown whether they regulate within-or between-meal parameters, or whether the absence of an ablation-induced bodyweight phenotype masks more subtle alterations in energy expenditure or physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that other regions, such as the ACB, LHA, MTN/PVT, and VTA, could mediate the regulatory effect of GLP-1RAs on food intake (21)(22)(23)(24)(25). Studies suggest a role for brain-derived GLP-1 in the control of eating and reward (80,81), but there is no evidence that peripherally administered GLP-1RAs can directly access GLP-1Rs in these regions, as demonstrated by the lack of fluorescently labeled semaglutide in these brain nuclei. Thus, activation of brain-derived GLP-1 would be necessary for peripherally circulating GLP-1/GLP-1RAs to engage GLP-1Rs in regions such as the ACB or VTA.…”
Section: Discussionmentioning
confidence: 99%
“…Preproglucagon (Gcg) is expressed in pancreatic a-cells, in enteroendocrine L-cells throughout the gut, predominantly in the distal ileum and colon, and in a population of neurons in the nucleus tractus solitarii (NTS) of the brainstem [52,84e89]. Diphtheria toxin-induced ablation of preproglucagon-positive neurons in the NTS demonstrated that this small population of neurons is the primary source of endogenous GLP-1 in the brain [90]. Cleavage sites within the proglucagon molecule together with expression of specific prohormone convertase enzymes determines which smaller peptide molecules/hormones are formed, including glicentin (aa 1e69), glicentin-related pancreatic polypeptide (GRPP; aa 1e30), glucagon (aa 33e61), oxyntomodulin (OXM; aa 33e69), the major proglucagon fragment (MPGF; aa 72e158), and the glucagonlike peptides 1 (GLP-1; aa 72e107/108) and 2 (GLP-2; aa 126e 158) ( Figure 1 The expression of Gcg in the pancreas, intestine, and brain is under the control of a single promoter and is initiated from an identical transcription start codon ( Figure 2).…”
Section: Transcriptional Regulation Of Preproglucagon (Gcg)mentioning
confidence: 99%
“…As discussed above, in addition to enteroendocrine L-cells, GLP-1 is also produced in a discrete set of non-TH-positive neurons in the caudal portions of the NTS [86,148,346e348], and these hindbrain GCG þ positive neurons are the primary source of endogenous brain GLP-1 [90]. Either peripheral administration of leptin [349] or gastric balloon distention [350] acutely activates GLP-1-producing neurons in the NTS, as assessed by cFos immunoreactivity.…”
Section: Endocrine Regulation Of Central Glp-1 Secretionmentioning
confidence: 99%
See 1 more Smart Citation